Maximum Useable Frequency Prediction Using Vertical Incidence Data - Mudzingwa, Courage; Nechibvute, Action; Chawanda, Albert (2016)
The formulation of dependable propagation prediction techniques is of profound importance in the advancement of radio science and such techniques can be of engineering value. In this paper, a compact review of the propagation prediction methods and models for HF communication systems is presented. Propagation prediction challenges and some approaches for meeting these challenges are also described.The comparison between predicted and measured maximum useable frequency (MUF) is used for analysing the accuracy of the ITU-R P.533 and the Ray theory prediction methods in the Southern African region. ITU-R P.533 method was found to generally give a better agreement with the measured datathan did Ray theory method.